(Maghemite/Chitosan/Polypyrrole) nanocomposites for the efficient removal of Cr (VI) from aqueous media. Issue 1 (February 2021) - Reis, Edson da S.; Gorza, Filipe D.S.; Pedro, Graciela da C.; Maciel, Bruna G.; da Silva, Romário J.; Ratkovski, Gabriela P.; de Melo, Celso P.
Abstract: We report the preparation of a new hybrid magnetic nanocomposite (HMNC) based on maghemite (γ-Fe2 O3 ), chitosan (Chi), and polypyrrole (PPY), and its use in water remediation protocols. We prepared the γ-Fe2 O3 nanoparticles by a coprecipitation route in the presence of chitosan, whose role is to envelop the nanoparticles, easing the posterior incorporation of PPY chains. We characterized the resulting hybrid composites by scanning electron microscopy (SEM), X-ray diffraction (XRD), infrared (FTIR) spectroscopy, water contact angle, and magnetic measurements. The γ-Fe2 O3 @Chi@PPY HMNC exhibited spherical morphology, with an average diameter of 34 nm, and a saturation magnetization of 9.8 emu.g −1 . Due to this characteristic, these composites can be easily removed through the application of an external magnetic field. The HMNC showed their best capacity of removing Cr (VI) ions from aqueous media at pH 2.0, attaining a 100% degree of capture for concentrations below 10 mg.L −1, with a maximum removal capacity (301.2 mg.g −1 ) that is higher than those of other polypyrrole based materials discussed in the literature. Recycling studies showed that the HMNC presented excellent performance and could be reused in at least five consecutive adsorption/desorption cycles without significant losses in their original adsorption capacity. For allying high adsorbing characteristics to a simple manner of removal of the captured contaminant from aqueous media, this γ-Fe2 O3 @Chi@PPY HMNC appears as a very promising platform for wastewater treatment. Graphical Abstract: ga1 Highlights: The combined presence of Chi and PPY leads an increase of the HMNC adsorption capacity. The magnetic characteristics of the HMNC allow its easy recovery from liquid media. The HMNC can be recycled and used for five consecutive times. The HMNC is a promising cost-effective material for the efficient removal of Cr (VI) ions.